Oscillator characterization in time domain - Siah, Bing Yi (2011)
To characterize an oscillator in time domain, frequency stability and accuracy are the main issues. The term of accuracy can be defined as the deviation from the standard of the quantity that was being measured. Meanwhile, the term of Stability means the variation of measurement samples. In order to characterize the accuracy and stability of an oscillator, a large number set of frequency data can be calculated through statistical method named Allan Deviation. This project focuses on a method to investigate the frequency stability of the quartz crystal oscillator and synthesizers in time domain by using Allan Deviation.